We Need Them. They Will Do Much Better Without Us. A Review of Survival at Stake, by Poorva Joshipura - Venkatesh, G (Studia Ecologiae et Bioethicae, 2024)
Poorva Joshipura’s book Survival at Stake embarks on an interdisciplinary examination of ethical and scientific issues related to the treatment of animals, highlighting their impact on human well-being and the future of civilisation. The author, a dedicated activist affiliated with PETA, underscores the challenges posed by the exploitation of animals within the frameworks of intensive farming, laboratory experimentation, and the illegal wildlife trade. The critique illustrates how unethical practices can give rise to pandemics, the deterioration of biodiversity, and ecological imbalances. Moreover, the text advocates for a comprehensive, humanistic, and cross-disciplinary approach that reassesses and transforms the relationship between humanity and the animal world.